Public Goods and Technology of Consumption: A Comment - Zabalza, A. (Review of Economic Studies, 1977)
Journal Article Public Goods and Technology of Consumption: A Comment Get access A. Zabalza A. Zabalza London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 1, February 1977, Pages 193–194, https://doi.org/10.2307/2296987 Published: 01 February 1977 Article history Received: 01 October 1975 Accepted: 01 May 1976 Published: 01 February 1977